McGraw-Hill science navigator ([New York] McGraw-Hill, 1998)
Science Navigator contains scientific information for easy reference. It includes : McGraw-Hill Encyclopedia: full text of the McGraw-Hill Concise Encyclopedia of Science & Technology, fourth edition; McGraw-Hill Dictionary, with definitions for more than 105,000 common and specialized scientific terms from the McGraw-Hill Dictionary of Scientific and Technical Terms, fifth edition; McGraw-Hill Biographies: biographical sketches of 1,100+ important historical and contemporary scientists and engineers.
Keywords: Science -- Encyclopedias; Science -- Dictionaries; Science -- Biography